Konflik Batin Tokoh Utama pada Miniseri Kamen Rider Snipe: Episode Zero - Erlangga, Rio Arif; Nurita, Wayan (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2024)
This research discusses the inner conflict experienced by the character Hanaya Taiga in the film Kamen Rider Snipe: Episode ZERO. This thesis uses Kurt Lewin's conflict theory and also uses qualitative methods as a research method, where the results of data analysis are in the form of descriptive word explanations. The technique used in this research is the observation and note-taking technique where the data source is analyzed and then notes related to the occurrence of inner conflict in the character Hanaya Taiga. The results of this research found that the conflicts experienced by Hanaya Taiga were type 1 conflict, type 2 conflict, and also type 3 conflict. Keywords: inner conflict; Kamen Rider; main character; miniseries.